NEUTRINO BEAM BUNCH STRUCTURE RECONSTRUCTION WITH PRECISION TIMING IN THE ICARUS LIQUID ARGON TIME PROJECTION CHAMBER - Heggestuen, Anna Elizabeth, author; Wilson, Robert J., advisor; Mooney, Michael, committee member; Berger, Joshua, committee member; Brandl, Alexander, committee member (Colorado State University. Libraries, 2026)
The ICARUS detector has been operating smoothly since 2021 as the far detector in the ShortBaseline Neutrino (SBN) program at Fermilab, collecting neutrino interactions from both the Booster Neutrino Beam (BNB) and off-axis from the Neutrinos at the Main Injector (NuMI) beam. Analysis of neutrino interactions in ICARUS requires mitigation of substantial cosmogenic back- grounds. This is achieved by using an external Cosmic Ray Tagger (CRT) and a Photomultiplier Tube (PMT) system embedded in the liquid argon. The intrinsic neutrino beam bunch structure, inherited time structure from the Radio Frequency (RF) system used to accelerate the protons, can be resolved at the ICARUS detector using precise timing information. Located at shallow depth, ICARUS is exposed to a high flux of cosmic rays that can be mistakenfor neutrino interactions. To mitigate this background, the CRT and a 3-meter-thick concrete over- burden were installed. To better model backgrounds, ICARUS makes use of an overlay technique where simulated neutrino events are superimposed on detector beam-off data. PMTs installed within a Time Projection Chamber detect argon scintillation light emitted by high energy charged particles passing through the chamber and provide the event timing of neutrino interactions. The nanosecond-level beam bunch structure is reconstructed with the PMT system and can be used to further understand backgrounds and enhance neutrino physics capabilities. In this thesis, I will discuss background mitigation techniques using precision timing and present a novel technique to select neutrino events from our unbiased data stream using the beam bunch structure.